2016
DOI: 10.1111/exd.13118
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glyoxalase activity is associated with reduced expression of neurotrophic factors and pro‐inflammatory processes in diabetic skin cells

Abstract: Patients suffering from type II diabetes develop several skin manifestations including cutaneous infections, diabetic dermopathy, diabetic bullae and acanthosis nigricans. Diabetic micro- and macroangiopathy as well as diabetic neuropathy are believed to play a crucial role in the development of diabetic skin disorders. A reduced cutaneous nerve fibre density was reported in diabetic subjects, which subsequently leads to impaired sensory nerve functions. Using an innervated skin model, we investigated the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…Remarkably, the activity of glyoxalase I was reduced in diabetic fibroblasts as compared with non-diabetic fibroblasts ( Figure 4 B). Comparable observations have been obtained from human keratinocytes, with the expression of glyoxalase I being comparable in keratinocytes from diabetic and non-diabetic donors but with the activity being reduced in keratinocytes from diabetic donors [ 43 ]. In this study, the activity of glyoxalase I was found to be reduced upon treatment of dermal fibroblasts with MIF( Figure 4 D), suggesting that MIF activates a signalling pathway that negatively regulates glyoxalase I activity.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Remarkably, the activity of glyoxalase I was reduced in diabetic fibroblasts as compared with non-diabetic fibroblasts ( Figure 4 B). Comparable observations have been obtained from human keratinocytes, with the expression of glyoxalase I being comparable in keratinocytes from diabetic and non-diabetic donors but with the activity being reduced in keratinocytes from diabetic donors [ 43 ]. In this study, the activity of glyoxalase I was found to be reduced upon treatment of dermal fibroblasts with MIF( Figure 4 D), suggesting that MIF activates a signalling pathway that negatively regulates glyoxalase I activity.…”
Section: Discussionmentioning
confidence: 90%
“…However, the data on secretion of MIF and PICP exhibited relatively large values of the standard deviation and p -values higher than 0.05 ( Figure 2 ). Large values of the standard deviation and p -values higher than 0.05 seem to be associated with the usage of primary cells, e.g., the secretion of several pro-inflammatory factors from keratinocytes of diabetic donors tended to be increased (albeit non-significantly) [ 43 , 44 ]. A higher number of donors (if available) might help to find statistical significance.…”
Section: Resultsmentioning
confidence: 99%
“…Proteomic analysis on MGO-modified intra/extracellular proteins will likely unveil more protein glycation hot spots in patients with diabetes. Second, MGO-induced BMPC dysfunction was investigated in this study, but MGO affects various cell types that participate in diabetic wound repair, including keratinocytes and fibroblasts (49,50). Although beyond the scope of the current study, it would be interesting to evaluate the impact of pathophysiological levels of MGO on these cell types.…”
Section: Discussionmentioning
confidence: 99%
“…To better mimic the physiological environment of sensory neurons, several teams created 2D and 3D coculture models, including sensory neurons and various cell types such as Schwann cells [29][30][31], fibroblasts [30][31][32][33][34][35][36][37][38][39], endothelial cells [31,35,36], and/or keratinocytes [29,[31][32][33][34][35][36][37][38]40]. Indeed, some of these cells have been shown to modulate neurite growth [41], and one can expect a sensory neuron response to be closer to the in vivo response in a more physiological environment.…”
Section: Sensory Neuron Culture and Coculturementioning
confidence: 99%